Communication, Leadership, and Work Environment in Employee Performance - Gede Alit Tri Guna; Made Ary Metriana; Komang Krisna Heryanda (MASI Mandiri Edukasi, 2026)
Employee performance remains a critical challenge for hospitality organizations due to the high demands of service quality and internal organizational dynamics. This study addresses performance issues related to communication effectiveness, leadership practices, and the work environment, with the objective of analyzing the influence of these factors on employee performance in a hotel setting. The research applied a quantitative approach using a survey method, involving all employees of the hospitality organization as research participants. Data were collected through structured questionnaires and analyzed using multiple linear regression to examine both partial and simultaneous effects of communication, leadership, and the work environment on employee performance. The results indicate that communication, leadership, and the work environment each have a positive and significant effect on employee performance, both individually and collectively. Effective communication improves coordination and task clarity, leadership enhances motivation and direction, and a supportive work environment increases comfort and work engagement. These findings emphasize the importance of integrated managerial strategies that strengthen internal organizational factors. The study concludes that improving communication quality, leadership effectiveness, and workplace conditions is essential to enhancing employee performance and sustaining service excellence in the hospitality industry.